Regulatory focus in relationships and conflict resolution strategies - Rodrigues, D. L. (2019)
Motives for security (prevention focus) and advancement (promotion focus) influence goal pursuit, but less is known about how such motives operate in the relationship domain. Regulatory focus in relationships (RFR) is a dispositional trait specific to relationship motives, whereby relationship promotion facilitates effective conflict resolution strategies, and relationship prevention leads to conflict avoidance. This research sought to examine if RFR operates in conjunction with commitment, a relationship motive, to facilitate outcomes during relationship conflict. A correlational survey of 701 romantically involved heterosexuals in Portugal and Croatia revealed an interaction between RFR and commitment on conflict resolution strategies. Results showed that relationship promotion (vs. prevention) was associated with more constructive resolution strategies (e.g., constructive accommodation, greater mutual negotiation and less mutual blame), but this effect was greater for highly (vs. less) committed individuals. High commitment also facilitated individuals predominantly focused on relationship prevention to engage in more mutual expression of feelings and negotiation. No interaction emerged for destructive accommodation. These patterns were similar across the two countries. Findings suggest the need to consider the interplay of RFR and commitment on different relationship outcomes.